Efektifitas Media Video Penggunaan Spill Kit Terhadap Kemampuan Petugas di RS PKU Muhammadiyah Yogyakarta unit II - Sussy Listiarsasih (Universitas Muhammadiyah Yogyakarta, 2016)
Infection prevention and control programs areinclude to the important programs because the transmission of infection are particularly vulnerable occur in hospitals, especially from body fluid spills. Related to infectious body fluids, spill kit is used to handle it. The use of spill kits are made by the officer who first discovered the infectious body fluids. The study assessed the effectiveness of training with video media on ability of PKU Muhammadiyah Hospital Unit II officers to use spill kit. Qualitative research with action research that consisted of planning, action, observation, and reflection. The training was conducted by video media. The ability of officials assessed by a checklist based on Standard Operating Procedures (SOP) when pretest and posttest. Focus Group Discussion (FGD) also held after the training. The study was conducted during the months of November to December 2015. Data analysis of training value using paired T-Test as support data. Only 31.6% participants that can use spill kit properly before training and after training 100% participants can use spill kit properly that appropriate to SOP in the hospital. Additionally, many suggestion submitted by officers when FGD associated with the stages of use spill kit at PKU Muhammadiyah Hospital Unit II. There are differences in the ability of PKU Muhammadiyah Hospital officers Unit II in use spill kit before and after training with video media. The SOP that already exist should be revised. There should also be disseminated more adequately on the use of spill kit at PKU Muhammadiyah Hospital Unit II.